Characteristics of dietary supplements containing in its composition glutathione (GSH) available in Poland - Hanna Czeczot; Joanna Witwicka (Polish Pharmaceutical Society, 2020)
Glutathione (GSH) is a endogenous , low molecular weight thiol compound. It has a wide spectrum of biological activity in the body. It is an important element of the antioxidant system that protects cells against the effects of oxidative stress. As an antioxidant, GSH inactivates free radicals and reactive forms of oxygen and nitrogen in enzymatic and non-enzymatic reactions, regenerates other antioxidants, e.g. vitamins C and E, maintains - SH groups in proteins in a reduced state, participates in the detoxification of xenobiotics. The decrease in GSH concentration occurs in many diseases and in the aging process. Increasing the level of GSH in the body's cells is possible by consuming dietary components containing GSH or amino acids (especially cysteine) for its endogenous synthesis and supplementation with GSH pharmaceutical preparations. The aim of the study was to characterize dietary supplements available in Poland containing glutathione (GSH). The analysis covered 39 supplements from GSH, which were available in Poland. Their characteristics include: place / country of production; type of preparations (single and multi-component); bioavailability of GSH contained therein - preparations in the liposome formula (lipophilic GSH) and in the non-liposome formula (non-lipophilic GSH); pharmaceutical form in which these preparations were available on the commercial offer and GSH content in supplements. Among 39 GSH supplements, there were 24 single-component and 15 multi-component preparations. The largest number of GSH supplements available in Poland came from the USA and Great Britain. Among GSH supplements, there were 15 liposome (lipophilic) formula preparations, of which 12 were lipophilic one-component and 3 multi-component and 24 non-liposome (non-lipophilic) formula preparations - 12 single and 12 multi-component. Capsules, gel, liquid and tablets were the most common pharmaceutical form among all analyzed GSH supplements. The rarest pharmaceutical form was lozenges, aerosol, powder and ampoule. Analysis of GSH supplements available in Poland showed that in one single dose of the preparation was from 18 mg to 750 mg GSH. The most common dose was 250, 450 and 500 mg GSH in a single dose. One-component supplements most often contained 450 mg, then 250 and 500 mg GSH, while multi-component supplements - 250 mg GSH.